2023
DOI: 10.14444/8531
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Paraspinal Muscular Morphology, Spinopelvic Parameters, and Back Pain: A Comparative Cohort Study

Enrico Giordan,
Giacomo Drago,
Roberto Zanata
et al.

Abstract: Background: The relationship between paraspinal muscle degeneration and low back pain (LBP), disability, and structural changes has been investigated in the literature, but it is still a matter of debate. We differentiated paraspinal muscle magnetic resonance imaging by quality and quantity, focusing on fatty infiltration (FI) and paraspinal muscles cross-sectional area (CSA) from T12 to S1 in patients with and without chronic LBP. We aimed to determine whether paraspinal muscle quantity (CSA) and quality (FI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Reiter studied the relationship between energy metabolism and body composition of skeletal muscle in healthy adults and believed that muscle fat infiltration not only leads to a decrease in muscle strength and endurance, but also causes muscles to lose elasticity and repairability [16] . A large number of studies have shown that [17][18][19] paraspinal muscle fat infiltration is common in elderly people, especially in elderly patients with spinal degenerative changes. Paraspinal muscle fat infiltration not only leads to damage of paraspinal muscle strength and decreased spinal stability, affecting the normal physiological function of whole body movement, but also increases the failure rate of spine surgery and affects the effect of postoperative rehabilitation and extends the recovery time under severe infiltration of adipose tissue [10,20] .…”
Section: Fat Infiltration Of Paraspinal Musclesmentioning
confidence: 99%
“…Reiter studied the relationship between energy metabolism and body composition of skeletal muscle in healthy adults and believed that muscle fat infiltration not only leads to a decrease in muscle strength and endurance, but also causes muscles to lose elasticity and repairability [16] . A large number of studies have shown that [17][18][19] paraspinal muscle fat infiltration is common in elderly people, especially in elderly patients with spinal degenerative changes. Paraspinal muscle fat infiltration not only leads to damage of paraspinal muscle strength and decreased spinal stability, affecting the normal physiological function of whole body movement, but also increases the failure rate of spine surgery and affects the effect of postoperative rehabilitation and extends the recovery time under severe infiltration of adipose tissue [10,20] .…”
Section: Fat Infiltration Of Paraspinal Musclesmentioning
confidence: 99%